Cross-cultural adaptation, reliability and validity of the Turkish version of the stroke exercise preference inventory - Arıkan, Halime; Sertel, Meral (Frontiers in Psychology, 2025)
IntroductionWhile studies on version adaptation, validity, and reliability are common, no tools exist in Turkish literature to assess exercise preferences in stroke patients. This research aimed to translate the Stroke Exercise Preference Inventory (SEPI) into Turkish and evaluate its validity and reliability in stroke patients.MethodsNinety stroke patients completed the SEPI, Exercise Benefits/ Barriers Scale (EBBS), Behavioral Regulation in Exercise Questionnaire (BREQ-2), Stroke-Specific Quality of Life Scale (SSQoLS), and Frenchay Activities Index (FAI). The SEPI was translated into Turkish using a standard forward-backward translation process. Psychometric properties such as structural and construct validity, test–retest reliability, and internal consistency were assessed.ResultsReliability analysis demonstrated high internal consistency for SEPI-13, with Cronbach’s α values of 0.931. Validity testing revealed a 3-factor structure for SEPI-13, explaining 69.029% of total variance. CFA confirmed the model with acceptable fit indices. Construct validity showed good correlations with EBBS (r = −0.771; p < 0.001) and BREQ-2 (r = from −0.541 to 0.732; p < 0.001) for convergent validity, while divergent validity was supported by weak correlations with SSQoLS (r = 0.165; p = 0.120) and FAI (r = 0.137; p = 0.197). No floor or ceiling effects were observed for SEPI-13.DiscussionThe Turkish SEPI is a reliable and valid tool for assessing exercise preferences in stroke patients, aiding their rehabilitation.